2009
DOI: 10.5039/agraria.v4i2a13
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da evapotranspiração de referência na região de Seropédica- RJ, utilizando lisímetro de pesagem e modelos matemáticos

Abstract: Este trabalho foi realizado com o objetivo de avaliar a estimativa da evapotranspiração de referência (ETo) para a região de Seropédica, Rio de Janeiro, correlacionando medidas obtidas em lisímetros de pesagem com os métodos de Penman-Monteith-FAO 56 (PMF), Hargreaves-Samani (HS), Camargo (CA), Priestley-Taylor (PT), Makking (MA) e Tanque Classe A (TCA). Os valores de ETo estimados por PMF, PT e MA se mostraram bem correlacionados àqueles determinados pelo lisímetro de pesagem, ao passo que os métodos de HS e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 3 publications
1
11
0
28
Order By: Relevance
“…The Makkink method was developed for climatic conditions in Wageningem, the Netherlands, and probably this was the reason for its performance. Other researchers also observed the same behavior in their research (BARROS et al, 2009;CAVALCANTE JR. et al, 2011;ARAÚJO et al, 2012;MAGALHÃES & CUNHA, 2012). The Linacre method is derived from Penman, estimating evapotranspiration through geographic data (latitude and altitude) and temperature, however, possibly denying of radiation and wind speed have turn it into unsatisfactory performance, corroborating PEREIRA et al (2009) andCUNHA (2012).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The Makkink method was developed for climatic conditions in Wageningem, the Netherlands, and probably this was the reason for its performance. Other researchers also observed the same behavior in their research (BARROS et al, 2009;CAVALCANTE JR. et al, 2011;ARAÚJO et al, 2012;MAGALHÃES & CUNHA, 2012). The Linacre method is derived from Penman, estimating evapotranspiration through geographic data (latitude and altitude) and temperature, however, possibly denying of radiation and wind speed have turn it into unsatisfactory performance, corroborating PEREIRA et al (2009) andCUNHA (2012).…”
Section: Resultssupporting
confidence: 52%
“…The Priestley-Taylor method was developed to estimate the evaporation of saturated surfaces in a non-saturated atmosphere, which is the nature's normal condition (BARROS et al, 2009;CAVALCANTE JR. et al, 2011) and its performance confirmed with what was observed by MOURA et al (2010); CUNHA (2012) andTAGLIAFERRE et al (2012b). The Camargo method is derived from the Thornthwaite method, and it works effectively in tropical climate and equatorial humid regions (CAVALCANTE JR. et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found by OLIVEIRA et al (2008) when comparing daily values of ETo by method HG and by lysimeter of hydraulic weighting, achieved value r 2 = 0.71 in Vitória de Santo Antão -PE. Nevertheless, the adoption of coefficient of determination r 2 as the only criterion of quality definition of methods is not adequate, since this index do not establish the type and magnitude of differences between estimated value by standard method and value predicted by estimation methods (BARROS et al, 2009). Thereby, the analysis of coefficient of correlation and standard error of estimation are auxiliaries in result interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of conducted research varied extremely, since each region present peculiar climate characteristics and the estimation methods of ETo exhibits problems of precision and accuracy, mainly because of the non-adjustment of model coefficients and sensors accuracy (BARROS et al, 2009). These empirical methods are based on observations and statistical analysis, generally adequate for a climate condition or specific region (FOOLADMAND & AHMADI, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores avaliaram o método PM comparando-o com lisímetros, e concluíram que esse é o método mais eficiente para estimar a ET0 (BARROS et al, 2009;SOUZA et al, 2011). Entretanto, este método necessita do conhecimento de vários elementos meteorológicos, que nem sempre se encontram disponíveis (MARTÍ et al, 2015).…”
Section: Introductionunclassified